To Study the Properties of Biopolymers: Natural Silk Fibroin (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
All polymers are made of repetitive units called monomers. Biopolymers often have a well-defined structure, though this is not a defining characteristic. Fibroin is an insoluble protein present in silk produced by numerous insects, such as the larvae of Bombyx mori, and other moth genera such as Antheraea, Cricula, Samia. The silk worm produces fibroin with three chains, the light, heavy, and the glycoprotein.